Dampak Pandemi Covid-19 Terhadap Kegiatan Keislaman Remaja Masjid Farida Kelurahan Damar Sari, Kecamatan Padang Hilir, Kota Tebing Tinggi - rizkia amar (Medan Resource Center, 2021)
The Covid-19pandemic that has attacked the world from the end of 2019 until now has caused many impacts in everyday human life. This impact can be seen from all fields, including in the religious field, one of which has an impact on the Islamic activities of one of the youth mosques in Tebing Tinggi City, namely the Farida Mosque Youth (Remafa). This research aims to determine the impact of the Covid-19 pandemic on the Islamic activities of the Farida Mosque Youth, Damar Sari Village, Padang Hilir District, Tebing Tinggi City. This type of research is field research with a qualitative approach that produces descriptive data in the form of writing about facts that occur in the field. Data collection techniques by means of interviews, observation and documentation. The results of the study show that the Covid-19pandemic has greatly impacted the Islamic activities of the Farida Mosque Youth. This impact can be seen from the many prohibitions and postponements of Islamic activities that are usually carried out by the Farida Mosque Youth, such as the abolition of the celebration of Islamic holidays, namely the commemoration of the Birthday of the Prophet Muhammad and Isra’ Miraj of the Prophet Muhammad SAW in 2020. In addition, activities also do not run as usual, such as a reduction in the time or duration of the tarawih prayer and tadarus of the Koran, it is also obligatory to use health protocols in worship at this time.